Efek Moderasi Tax Morale Pada Pengaruh Sikap Free Rider Dan Materialism Terhadap Tax Evasion - Dama Hirdayani Tuasikal; Zumratul Meini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the moderating effect of tax morale on the influence of free rider attitudes and materialism on tax evasion. The research method used is quantitative. The data collection technique in this study is primary data by distributing questionnaires and the population in this study is individual taxpayers. The sampling technique used was purposive sampling with a total sample of 100 individual taxpayers. The data analysis method used in this research is Structural Equation Modeling (SEM) using the SMART PLS v.03 application. The results showed that free rider attitudes and materialism had a positive effect on tax evasion, while tax morale did not moderate the effect of free rider attitudes and materialism on tax evasion. This shows that a taxpayer who has a free rider attitude enjoys the facilities provided but is reluctant to pay taxes, thus triggering tax evasion. Likewise, taxpayers who have materialism tend to prioritize the ownership of luxury goods so that paying taxes is something that is avoided. Tax morale cannot strengthen or weaken the influence of free rider attitudes and materialism on tax evasion, this shows that taxpayers in this research sample obey tax regulations not on the basis of self-awareness. Keywords: Tax Morale, Free Rider, Materialism, Tax Evasion.